Specialized Roles of Human Natural Killer Cell Subsets in Kidney Transplant Rejection - Kildey, Katrina; Francis, Ross S.; Hultin, Sebastian; Harfield, Michelle; Giuliani, Kurt; Law, Becker M. P.; Wang, Xiangju; See, Emily J.; John, George; Ungerer, Jacobus; Wilkinson, Ray; Kassianos, Andrew J.; et al. (Frontiers in Immunology, 2019)
BACKGROUND: Human natural killer (NK) cells are key functional players in kidney transplant rejection. However, the respective contributions of the two functionally distinct human NK cell subsets (CD56bright cytokine-producing versus CD56dim cytotoxic effector) in episodes of allograft rejection remain uncertain, with current immunohistochemical methods unable to differentiate these discrete populations. We report the outcomes of an innovative multi-colour flow cytometric-based approach to unequivocally define and evaluate NK cell subsets in human kidney allograft rejection. METHODS: We extracted renal lymphocytes from human kidney transplant biopsies. NK cell subsets were identified, enumerated and phenotyped by multi-colour flow cytometry. Dissociation supernatants were harvested and levels of soluble proteins were determined using a multiplex bead-based assay. Results were correlated with the histopathological patterns in biopsies – no rejection, borderline cellular rejection, T cell-mediated rejection (TCMR), and antibody-mediated rejection (AMR). RESULTS: Absolute numbers of only CD56bright NK cells were significantly elevated in TCMR biopsies. In contrast, both CD56bright and CD56dim NK cell numbers were significantly increased in biopsies with histopathological evidence of AMR. Notably, expression of the activation marker CD69 was only significantly elevated on CD56dim NK cells in AMR biopsies compared with no rejection biopsies, indicative of a pathogenic phenotype for this cytotoxic NK cell subset. In line with this, we detected significantly elevated levels of cytotoxic effector molecules (perforin, granzyme A and granulysin) in the dissociation supernatants of biopsies with a histopathological pattern of AMR. CONCLUSIONS: Our results indicate that human NK cell subsets are differentially recruited and activated during distinct types of rejection, suggestive of specialised functional roles.